A TRIBUTAÇÃO AUTÓNOMA EM PORTUGAL: UM CASO ESPECIAL DE TRIBUTAÇÃO DAS SOCIEDADES? - Dinis, Ana (2022)
In Portugal, the increasing number of autonomous taxation, reporting to susceptible situations of high risk of tax evasion, become gradually an alternative source of tax revenue, with particular corporate impact. Such taxation is for the vast majority of societies, with a low turnover, a significant percentage of tax paid. Moreover, the existence of autonomous taxation distorts the logic of Corporate Income Taxation (IRC), given that taxing expenses rather than income, leads to which it has lost some of its features, including being a tax on corporate profits. Thus, it is our objective to analyze, in a critical perspective, the role and the impact of autonomous taxation on corporate taxation in Portugal.